Chuyển đổi số trong giáo dục đại học: Khái niệm, sự phát triển và kiến nghị giải pháp - Nguyễn, Đức Ca; Đinh, Văn Thái (Tạp chí Giáo dục, 2024)
In response to the strong ongoing demand for digital transformation, the Education sector, particularly higher education institutions, has identified its pioneering mission in carrying out this task. This contributes to shortening the process of innovation, enhancing the quality of education and training, and making a positive contribution to the national digital transformation process. Digital transformation aims to meet the new requirements for training high-quality human resources capable of creativity and quickly absorbing global scientific and technological advancements, serving the country's development in the current phase. It is necessary for universities in the current context to correctly understand digital transformation, correctly recognize the advantages, difficulties and limitations, thereby proposing some solutions to make the digital transformation process in higher education go smoothly, and at the same time help higher education institutions have a roadmap for implementing reasonable and successful digital transformation to quickly improve the quality and effectiveness of training. This is very important for universities in the current context.